Pengaruh Kualitas Produk Dan Brand Awareness Terhadap Kepuasan Pelanggan UMKM Pocong Pancong di Kota Malang - Biasmoro, Bramanta Beckham; Permatasari, Ita Rifiani; Rachmi, Asminah (Jurnal Serambi Ekonomi dan Bisnis, 2024)
In a growing business world, characterized by the emergence of new types of businesses. The culinary field is one of the business fields that are in demand by business people. Customer satisfaction is quite important in the culinary business. Pocong Pancong MSMEs is one of the culinary businesses that strives to increase Customer Satisfaction through Product Quality and Brand Awareness strategies. This research aims to test and evaluate the impact of Product Quality and Brand Awareness on Customer Satisfaction of Pocong Pancong MSMEs in Malang City, either partially or simultaneously. This research is a type of quantitative research with statistical analysis. In this research, data was collected by distributing to 115 respondents. Regarding respondents in this study, namely consumers of Pocong Pancong MSMEs in Malang City. The sampling method used was purposive random sampling. In this study, data was collected uses methods with questionnaires and also observations. The data analysis used is multiple linear regression, t testing and F testing. The results of the research are partial and also simultaneous, product quality and brand awareness have an impact on customer satisfaction. And it is hoped that business persons can increase customer satisfaction through developing product quality and creating good brand awareness.